2016
DOI: 10.14814/phy2.12698
|View full text |Cite
|
Sign up to set email alerts
|

PGC-1αpromotes exercise-induced autophagy in mouse skeletal muscle

Abstract: Recent evidence suggests that exercise stimulates the degradation of cellular components in skeletal muscle through activation of autophagy, but the time course of the autophagy response during recovery from exercise has not been determined. Furthermore, the regulatory mechanisms behind exercise‐induced autophagy remain unclear, although the muscle oxidative phenotype has been linked with basal autophagy levels. Therefore, the aim of this study was to investigate the role of the key regulator of muscle oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
57
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 34 publications
5
57
1
3
Order By: Relevance
“…; Halling et al. ; Brandt et al. ) and in part with a previous study in humans showing an increase in LC3b mRNA content in skeletal muscle in response to acute ultra‐endurance running (Jamart et al.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…; Halling et al. ; Brandt et al. ) and in part with a previous study in humans showing an increase in LC3b mRNA content in skeletal muscle in response to acute ultra‐endurance running (Jamart et al.…”
Section: Discussionmentioning
confidence: 80%
“…; Halling et al. ). Moreover, previous mouse studies have shown an increase in LC3II protein in response to an acute bout of endurance exercise (Grumati et al.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…22 Littermate TG and wild-type (WT) mice were obtained by crossing heterozygous TG mice with WT mice and the genotype was determined by PCR as previously described. 20 In addition, unpublished data from our group show that there is no significant difference in PGC-1α mRNA in liver, visceral and subcutaneous adipose tissue between WT and TG mice, supporting muscle-specific PGC-1α overexpression. 20 In addition, unpublished data from our group show that there is no significant difference in PGC-1α mRNA in liver, visceral and subcutaneous adipose tissue between WT and TG mice, supporting muscle-specific PGC-1α overexpression.…”
Section: Micementioning
confidence: 68%
“…The present observation that PERK, eIF2α and IRE1α phosphorylation decreased with fasting may be an indication of energy sparing of the liver. 20 However, future studies are needed to clarify the role of autophagy in the liver. However, the observation that several other downstream UPR mRNAs increased with fasting indicates that UPR was activated in response to fasting and is in line with the observed increase in cleaved ATF6 protein in the current study.…”
Section: Discussionmentioning
confidence: 99%